Functional Regulation of KATP Channels and Mutant Insight Into Clinical Therapeutic Strategies in Cardiovascular Diseases - Wang, Zhicheng; Bian, Weikang; Yan, Yufeng; Zhang, Dai-Min (Frontiers in Pharmacology, 2022)
ATP-sensitive potassium channels (KATP channels) play pivotal roles in excitable cells and link cellular metabolism with membrane excitability. The action potential converts electricity into dynamics by ion channel-mediated ion exchange to generate systole, involved in every heartbeat. Activation of the KATP channel repolarizes the membrane potential and decreases early afterdepolarization (EAD)-mediated arrhythmias. KATP channels in cardiomyocytes have less function under physiological conditions but they open during severe and prolonged anoxia due to a reduced ATP/ADP ratio, lessening cellular excitability and thus preventing action potential generation and cell contraction. Small active molecules activate and enhance the opening of the KATP channel, which induces the repolarization of the membrane and decreases the occurrence of malignant arrhythmia. Accumulated evidence indicates that mutation of KATP channels deteriorates the regulatory roles in mutation-related diseases. However, patients with mutations in KATP channels still have no efficient treatment. Hence, in this study, we describe the role of KATP channels and subunits in angiocardiopathy, summarize the mutations of the KATP channels and the functional regulation of small active molecules in KATP channels, elucidate the potential mech-anisms of mutant KATP channels and provide insight into clinical therapeutic strategies.